La NIC 16 en la Unidad Educativa ‘Pensionado Olivo’ de Riobamba, durante el período enero-diciembre de 2023. - Tubón Ambo, Iván Andrés (2025)
This research focuses on how International Accounting Standard 16 (IAS 16) is being implemented at the educational institution 'Pensionado Olivo' in Riobamba, during the period from January to December 2023. The objective is to analyze the fixed asset control processes and assess how they impact asset management. The methodology used was descriptive, with a qualitative approach and a non-experimental cross-sectional design. The institution's human resources were considered as part of the studied population. Through the observation technique, the physical condition of the assets, their location, the control exercised over them, and how the implementation of technology aids in more accurate record-keeping were verified. In addition, a survey with eleven questions was conducted for the accountant, along with an interview that revealed her knowledge of IAS 16. The results showed partial compliance with the standard. Deficiencies were identified in the estimation of residual value, the lack of formal accounting policies, the absence of asset impairment assessment and limitations in the disclosure of information in the financial statements. It was also observed that the institution does not have an automated system for fixed asset control, which hinders efficient technical management. In summary, a system should be implemented to control the fixed assets and align with the guidelines of IAS 16, which will improve accounting management, the presentation of financial statements, and decision-making within the institution. This solution will significantly contribute to transparency, traceability, and efficiency in the management of the resources of the Educational Unit.